Validating power makes communal narcissists less communal - Giacomin, Miranda; Jordan, Christian H. (My University, 2015)
What motivates communal self-enhancement? Paulhus and John [1998. Egoistic and moralistic biases in self-perception: The interplay of self-deceptive styles with basic traits and motives. Journal of Personality, 66, 1025–1060] posit that agentic and communal self-enhancement biases are independently motivated by needs for power and approval, respectively. In contrast, the agency-communion model of narcissism [Gebauer, J. E., Sedikides, C., Verplanken, B., & Maio, G. R. (2012). Communal narcissism. Journal of Personality and Social Psychology, 103, 854–878] posits that communal narcissists' communal self-enhancement is driven by the need for power. We examined whether validating a sense of power affects the communal behavior and self-perceptions of communal narcissists. We observed that communal narcissists behaved less communally (Study 1) and displayed less communal self-enhancement (Study 2) when their need for power is validated rather than threatened. Consistent with the agency-communion model of narcissism, these results suggest communal narcissists are indeed motivated by the need to validate power.
Keywords: narcissism; communal narcissism; power; self-enhancement; agency; communion